Applied economic history as practical historicism: Encouraging policymakers to reason with the past - Christopher L. Colvin; Andrew Dorman; David Jordan; Duncan Needham (Queen's University Centre for Economic History (QUCEH), 2026)
This paper examines how applied history can contribute to policymaking when understood as a way of structuring judgement under uncertainty rather than as a source of policy lessons or predictions. It argues that economic history is particularly well suited to facilitating this role because it combines institutional analysis with disciplined comparison of plausible alternatives and close attention to temporal constraints. Distinguishing between micro-pedagogical and macro-institutional applications, the paper analyses two sites of practice: (1) a historically grounded policy simulation used to train early-career civil service economists delivered by the Centre for Economics, Policy and History, a research centre based in Belfast and Dublin; and (2) longer-term engagement between historians and policy advisers in Whitehall organised through History & Policy, an applied history forum. The paper concludes by clarifying the possibilities and limits of applied economic history as a contribution to reflective policy practice.
Keywords: A20; B40; N01; 330; applied economic history; historical uncertainty; policy pedagogy; practical historicism